Construction of precast segmental box girder bridge using overhead gantry - a case study - Salleh @ Mohamed Salleh, Jazlan (2006)
The bridge construction utilizing the concept of erecting the precast segmental panel has been a chosen method for bridge construction within restricted area. This method has been successfully exhibit the constructability within the urban area and also crossing the wide water body, valley and existing highway or railroad. The suitability of this method of construction is depending on the availability of working space, which govern the major cause in selection of this construction method. The aim and objective are to study the problem in the manufacturing the segment and segment erection. This master project has studied the procedures in construction of precast segmental box girder bridge by balance cantilever method using the overhead gantry. This project also studied the segment manufacturing procedures and discovers some problem problems faced in segment manufacturing that is interesting and need to expose for awareness to the bridge professional. The segment erection procedures and sequence also has been studied and the related problems have been highlighted and need further study by the professional bridge designers and constructors. The study has been conducted by direct structured interview and questionnaire with the bridge expertise. The bridge professional from consultants, segment manufacturer, main contractors and specialist sub contractor have shared their knowledge, technical know-how and experience and has been elaborated in details in this project. The finding is very interesting and it has exposed the problem related to the segmental bridge construction that need further study by the bridge expertise. This study also recommended some idea about working concurrently and simultaneously without fragmentation that could lead to errors. It is expected that by addressing the problem at early stage could assist the designer, manufacturer and constructor to foresee the problem and find the mitigation measures thus could eliminate the errors that may occurs in manufacturing the segment and erection on site.